Histone H4 underacetylation in plant facultative heterochromatin - Buzek, J; Riha, K; Siroky, J; Ebert, I; Greilhuber, J; Vyskot, B (Biological chemistry, 1998)
It has been recently shown that facultative heterochromatin in some phyla is H4 and H3 histone underacetylated. Here we present H4 acetylation analyses in a monocotyledonous plant species, Gagea lutea, whose pentaploid endosperm nuclei possess prominent facultative heterochromatin regions. This heterochromatin is attributed to three chromosome sets originated from the chalazal polar nucleus of the embryo sac. We have previously shown that some parts of this heterochromatin contain heavily methylated DNA, but not all the heterochromatin is hypermethylated. In this report we demonstrate that this facultative heterochromatin is characterised by a conspicuous depletion of histone H4 acetylation at N-terminal lysine residues 5, 8, and 12, but not 16. Endosperm metaphases stained with antiserum against H4Ac5 indicated some heavily labelled chromosomes, while the others displayed no signal (presumably those coming from the three heterochromatinised chromosome sets). Western blotting analyses have shown that the antisera used, designed to detect human H4 histones, are suitable to recognise specific isoforms of acetylated H4 histones in plants and that the most abundant H4 in G. lutea leaves occurs in its diacetylated isoform. We conclude that flowering plants, similarly to protozoa, yeasts and animals, evolved core histone acetylation/deacetylation as a long-term transcriptional control mechanism to establish and/or transmit epigenetic information on gene expression.
Keywords: western blotting; histony; antisérum; acetylace; Liliaceae; heterochromatin; Histones; Blotting, Western; Immune Sera; buněčné jádro; Cell Nucleus; liliovité; Heterochromatin; Acetylation